PENERAPAN EDUKASI PEMANFAATAN TEKNOLOGI INFORMASI DAN KOMUNIKASI BERBASIS KOMPUTER PADA PESERTA DIDIK SMA PETTA BARINGENG SOPPENG - Nuzulul Afia Idris; Andri Sugyanto; Andi Syadaruddin; Andi Rosdiana; Yusri Yusri (Universitas Ichsan Sidenreng Rappang, 2026)
The ever-expanding role of Information and Communication Technology (ICT) and its various aspects consistently have a positive impact on life. Therefore, it is crucial for students to learn Information and Communication Technology (ICT) effectively. However, the lack of opportunities for students to develop their potential in using computer applications hinders their technological skills. As a concrete step, this educational program focuses on utilizing IT for students at Petta Baringeng High School, Soppeng. The program's primary goal is to enhance student knowledge and make them independent, creative, and skilled in learning computer software, particularly Microsoft Word and Microsoft PowerPoint, as well as introducing them to computer hardware. This will equip them to utilize technology effectively and sustainably in the future.